2012
DOI: 10.1152/jn.00297.2011
|View full text |Cite
|
Sign up to set email alerts
|

Neural coding of continuous speech in auditory cortex during monaural and dichotic listening

Abstract: The cortical representation of the acoustic features of continuous speech is the foundation of speech perception. In this study, noninvasive magnetoencephalography (MEG) recordings are obtained from human subjects actively listening to spoken narratives, in both simple and cocktail party-like auditory scenes. By modeling how acoustic features of speech are encoded in ongoing MEG activity as a spectrotemporal response function, we demonstrate that the slow temporal modulations of speech in a broad spectral regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
471
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 457 publications
(524 citation statements)
references
References 64 publications
52
471
1
Order By: Relevance
“…Auditory studies have similarly investigated the impact of pre-target oscillatory state but did so mostly in paradigms in which oscillations were driven by discrete and periodic stimuli. These auditory studies found effects mostly at lower frequencies, such as the delta and theta bands (Luo and Poeppel, 2007;Lakatos et al, 2009;Schroeder and Lakatos, 2009;Stefanics et al, 2010;Besle et al, 2011;Ding and Simon, 2012). Our results reiterate this importance of theta-band over alpha-band oscillations in auditory cortex for stimulus detection.…”
Section: Role Of Oscillatory State For Perceptionsupporting
confidence: 84%
See 4 more Smart Citations
“…Auditory studies have similarly investigated the impact of pre-target oscillatory state but did so mostly in paradigms in which oscillations were driven by discrete and periodic stimuli. These auditory studies found effects mostly at lower frequencies, such as the delta and theta bands (Luo and Poeppel, 2007;Lakatos et al, 2009;Schroeder and Lakatos, 2009;Stefanics et al, 2010;Besle et al, 2011;Ding and Simon, 2012). Our results reiterate this importance of theta-band over alpha-band oscillations in auditory cortex for stimulus detection.…”
Section: Role Of Oscillatory State For Perceptionsupporting
confidence: 84%
“…Previous work has shown that auditory entrainment prevails for oscillations Ͻ10 Hz (Luo and Poeppel, 2007;Kerlin et al, 2010;Ding and Simon, 2012;Ng et al, 2012). For our experimental setup, we found that centrally located auditory driven oscillations between 2 and 6 Hz exhibited the strongest entrainment as measured using the oscillatory ITC (see Materials and Methods and Fig.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations